Isolation of anti-inflammatory compounds from Sambucus ebulus leaves through in vitro activity-guided fractionation - Atay, İrem; İlter, Ayça Zeynep; Bagatur, Yeşim; Telci, Dilek; Gören, Ahmet; Kırmızıbekmez, Hasan; Yeşilada, Erdem (Georg Thieme Verlag, 2015)
The in vitro anti-inflammatory effects of subextracts (n-hexane, chloroform, ethyl acetate, n-butanol, remaining water) of the methanol extract of the leaves of Sambucus ebulus L. (Adoxaceae) were investigated for their inhibitory activities on the activation of Nuclear factor kappa B (NF-?B) on lipopolysaccharide induced Raw 264.7 cells. The n-hexane, chloroform and ethyl acetate subextracts inhibited NF-?B activation at 50, 100 and 100 µg/mL concentrations, respectively. Two flavonoid mixtures [quercetin-3-O-?-D- glucopyranoside, quercetin-3-O-?-D-galactopyranoside], two flavonoids [isorhamnetin-3-O- ?-D-glucopyranoside (1), isorhamnetin-3-O-rutinoside (2)] were isolated from ethyl acetate subextract. 10-O-acetylpatrinoside (3) and a new iridoid [Sambulin B (4)] was obtained from chloroform and n-hexane subextracts respectively. Structures were elucidated by NMR and MS. The compounds exerted inhibitions between 30 – 80% on NF-?B. Flavonoids were applied to cells at 25, 50, 75 and 100 µg/mL concentrations. Sambulin B was applied at 6,25, 12,5, 25 and Sambulin A applied at 12,5, 25 and 50 µg/mL concentrations.
63rd International Congress and Annual Meeting of the Society-for-Medicinal-Plant-and-Natural-Product-Research (GA) -- August 23-27, 2015 -- Budapest, Hungary
WOS: 000367558100418
Keywords: Isolation; Sambucus; Ebulus